Effect Of Sex And Body Region On Wool Characteristics Of Correidale Sheep (Ovis Aris) (Applied Biological Research, 2017)
The end use suitability of wool is influenced by its characteristics, varying between species, individuals and sex. Wool characteristics of Correidale sheep  was studied to evaluate its suitability for developing region-wise grading  ystem for better marketability. Twelve Corriedale sheep (>1 year), six each  from both sexes were taken for the study. About 40 g wool sample was  collected by shearing from five body regions viz; back, neck, shoulder, flank  and thorax. Fibre diameter, medullation, staple length, crimp frequency, fibre  length, scouring yield, grease, burr, suint and bundle strength was evaluated.  Significant differences were observed in the number of crimps and staple  length between sexes while diameter, medullation, fibre length, scouring yield,  burr, grease, suint and bundle strength showed no significant variation. In  general, the average quality in terms of diameter was better at shoulder  followed by neck, thorax, flank and back. It was concluded that region-wise  grading of wool at harvesting may provide better marketability.
Keywords: Correidale; fleece; marketability; sheep; woolcharacteristics